Ride into trouble [large type] - Stone, R. W. (Center Point Large Print, 2020)
Lt. Ed Preston is returning to his cavalry fort after being on leave when he is mistaken for a bank robber. He is arrested, placed on trial and sent to prison to serve years of hard labor for a crime he did not commit. Forced to endure horrible conditions and brutal treatment he is left with no choice but to plan his escape and then to search the west for the man who is truly guilty of the crime in an attempt to clear his name and regain his life.